Peranan Kepolisian Dalam Menanggulangi Tindak Pidana Pungutan Liar Di Lembaga Pendidikan (Studi Pada Polresta Barelang) - Delfani Laia; Padrisan Jamba (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
In the case of extortion ever happened in the city of Batam. The extortion is in the process of Accepting New Students at SMPN 10 Batam City. The indications of PPDB fraud have actually become suspicion in the community, but in law enforcement in the case of extortion is quite complicated because it is designed systematically in such a way that it will be difficult later in the proof process. Obtained evidence in the form of Money, Proof of Acceptance of New Students, and SK. This investigation is in accordance with KUHAP Article 1 Paragraph (19), the investigation which took place at SMPN 10 Batam City was said to be caught red-handed, the suspect was found at that time. The obstacles of the police in this illegal levy are: Lack of information from the public about the crime of illegal levies and is covered up in carrying out illegal levies at schools, thus hampering the police. Efforts that can be made by the police are to appeal to each agency regarding legal sanctions when committing illegal levies and carrying out patterns of prosecution or punishment against illegal levies based on the legal provisions in the prevailing laws and regulations.